Localized processes of platformization: The example of Surabaya - Alessandra Renzi; Janna Frenzel (Big Data & Society)
This article analyzes how universalist paradigms for platform urbanism are being adapted, modulated, and subverted through an evolving platform ecosystem that is specific to the city of Surabaya, Indonesia's second largest city. We examine how processes of urban planning and city management are platformized, how specific groups of professionals and residents act as intermediaries between infrastructure and users and thereby facilitate the platformization process, and how these local iterations of platforms are informed by place-specific colonial and national history. By describing and tracing the genealogy of Surabaya's platform ecosystem, we demonstrate the specific ways in which it rationalizes city governance, shapes discourses on participatory citizenship and spatial planning, and redefine what counts as city infrastructure, innovation, and urban life in general. We argue that the modulation, adaptation, and resistance to platformization can only be understood by paying attention to the singularity of the milieu and tracing how visions of modernity and its sociotechnical assemblages are composed anew every time platform frameworks, tech tools, and discourses hit the ground.